New World Information and Communication Order and Its Changing Role in Nigerian Television Authority (NTA) Kano - Aondover , Eric Msughter; Oyeleye, Solomon A.; Aliyu, Maiwada Abdullahi (Universitas Islam Indonesia, 2023)
Media technologies have been considered freeing and empowering since the twentieth century, as they aid in enhancing human capacity. In the media and communication industries, technologies have aided human manipulation of mechanical and electronic processes. Arguably, social interactions were improved by extending audience reach, broadening coverage, changing time and location constraints, and bridging important gaps in information. In this context, this study used in-depth interviews as the research method, and thematic analysis was employed to analyze the data gathered based on the themes that emerged during the interviews. The population of the study consisted of 106 staff in the Nigerian Television Authority (NTA) Kano, and a purposive sampling technique was used to select 15 participants for the study. This study is premised on the Domestication and Technological Determinism Theories. The findings of the study revealed that quality information dissemination, good visualization, easy access to information, and quick spread of information to the target audience are among the factors responsible for the adoption of information technology in NTA Kano. The study concludes that there is a need for an increasing level of information technology, especially NTA Kano, to enhance adequate information dissemination. There is also a need to address financial difficulties, lack of constant training and retraining of staff, poor state of equipment or lack of maintenance, and lack of adequate funding to ensure the proper and smooth running of modern technologies in NTA Kano.